Trypanosoma cruzi-specific CD8+ T cells and other immunological hallmarks in chronic Chagas cardiomyopathy: Two decades of research - Puerta, Concepción J.; Cuellar, Adriana; Lasso, Paola; Mateus, Jose; Gonzalez, John M. (Frontiers in Cellular and Infection Microbiology, 2023)
Trypanosoma cruzi, the causal agent of Chagas disease, has coexisted with humans for thousands of years. Therefore, the parasite has developed several mechanisms of antigenic variability that has allowed it to live inside the cells and evade the host immune response. Since T. cruzi displays an intracellular cycle-stage, our research team focused on providing insights into the CD8+ T cells immune response in chronic Chagas cardiomyopathy. We began our work in the 2000s studying parasite antigens that induce natural immune responses such as the KMP11 protein and TcTLE, its N-terminal derived peptide. Different approaches allowed us to reveal TcTLE peptide as a promiscuous CD8+ T cell epitope, able of inducing multifunctional cellular immune responses and eliciting a humoral response capable of decreasing parasite movement and infective capacity. Next, we demonstrated that as the disease progresses, total CD8+ T cells display a dysfunctional state characterized by a prolonged hyper-activation state along with an increase of inhibitory receptors (2B4, CD160, PD1, TIM3, and CTLA-4) expression, an increase of specific terminal effector T cells (TTE), a decrease of proliferative capacity, a decrease of stem cell memory (TSCM) frequency, and a decrease of CD28 and CD3z expression. Thus, parasite-specific CD8+ T cells undergo clonal exhaustion, distinguished by an increase in late-differentiated cells, a mono-functional response, and enhanced expression of inhibitory receptors. Finally, it was found that anti-parasitic treatment induces an improved CD8+ T cell response in asymptomatic individuals, and a mouse animal model led us to establish a correlation between the quality of the CD8+ T cell responses and the outcome of chronic infection. In the future, using OMICs strategies, the identification of the specific cellular signals involved in disease progression will provide an invaluable resource for discovering new biomarkers of progression or new vaccine and immunotherapy strategies. Also, the inclusion of the TcTLE peptide in the rational design of epitope-based vaccines, the development of immunotherapy strategies using TSCM or the blocking of inhibitory receptors, and the use of the CD8+ T cell response quality to follow treatments, immunotherapies or vaccines, all are alternatives than could be explored in the fight against Chagas disease.